Coated battery diaphragm, preparation method and secondary battery

By regulating the distribution state of the adhesive microspheres in the ceramic coating of the lithium-ion battery separator, the problem of polymer coating affecting the permeability of the separator is solved, and the balance of the adhesion strength, breathability and powder loss rate of the separator is achieved, and the battery performance is improved.

CN119786881APending Publication Date: 2025-04-08SINOMA LITHIUM BATTERY SEPARATOR CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411996583.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Adding polymer coating to the ceramic coating of existing lithium-ion battery separators will affect the breathability of the separator, resulting in a decrease in battery conductivity and affecting charge and discharge performance.

Method used

By regulating the distribution state of the adhesive microspheres in the diaphragm ceramic coating, some of the adhesive microspheres protrude from the outer surface of the ceramic coating to form a single point bonding area, improving the bonding strength of the diaphragm while maintaining high breathability and conductivity.

Benefits of technology

The balance of diaphragm bond strength, breathability and powder loss rate is achieved, which improves battery performance and extends battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786881A_ABST
    Figure CN119786881A_ABST
Patent Text Reader

Abstract

According to the coated battery diaphragm provided by the test embodiment of the invention, a ceramic coating embedded with viscous microspheres is coated on a single surface or double surfaces of a base diaphragm, part of the viscous microspheres are arranged to be convex on the outer surface of the ceramic coating, and the volume sum of the parts, protruding out of the outer surface, of the microspheres accounts for 20-80% of the volume sum of the microspheres. According to the invention, the viscous microspheres are embedded and distributed in the ceramic coating and do not completely cover the surface of the ceramic coating; the adhesive microspheres at the protruding parts provide a considerable number of single-point bonding areas for the diaphragm, so that the bonding strength of the diaphragm is effectively improved, meanwhile, relatively high air permeability and relatively high conductivity are reserved for the diaphragm, the cohesiveness, the air permeability and the powder falling rate of the diaphragm are balanced, and the performance of the battery diaphragm is optimized. The invention also provides a preparation method of the coated battery diaphragm and a secondary battery containing the coated battery diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery separators, and in particular relates to a coated battery separator and a preparation method thereof, as well as a secondary battery using the coated battery separator. Background Art

[0002] Lithium-ion batteries have been widely used in portable devices due to their high energy density, good cycle performance, and no memory effect. As the application scenarios of lithium-ion batteries continue to increase, higher and higher requirements are placed on the performance and safety of lithium-ion batteries.

[0003] As one of the key components of lithium-ion batteries, battery separators are located between the positive and negative electrodes of the battery to isolate the positive and negative electrodes and conduct lithium ions. The choice of separator material directly affects the performance and safety of the battery. A separator with excellent performance can prevent uneven chemical reactions inside the battery, ensure the safety and stability of the battery, improve the performance of the battery, and extend the life of the battery. As for the material of the separator, polyolefin materials have been used as lithium battery separators in the early stage of lithium battery research and development due to their chemical stability, good insulation properties, appropriate pore size and porosity, mechanical strength and flexibility. To this day, they are still widely used in the field of lithium battery manufacturing. Traditional polyolefin separators have the defects of insufficient thermal stability, uneven pore structure, easy shrinkage at high temperature, causing internal short circuits in the battery and thermal runaway. In order to improve the performance of polyolefin separators, surface modification of the separator is an effective method, and ceramic coating is usually performed on the surface of the polyolefin separator. Since polyolefin is a hydrophobic material and the surface of common ceramic coating is generally hydrophilic, the bonding strength between the two is low. During high-rate cyclic charge and discharge, the diaphragm coating may fall off or the ceramic coating particles may adhere to the positive and negative electrodes. In addition, the polyolefin diaphragm has poor wetting and liquid retention capabilities for the electrolyte, which reduces the conductivity, limits the charge and discharge rates of lithium batteries, and affects the performance of ceramic diaphragms in lithium-ion batteries.

[0004] In order to improve the above defects, the prior art further adopts the method of adding a polymer coating to the ceramic coating, but usually the coating method of this polymer coating is to fully cover the surface of the ceramic coating. Although it can improve the adhesion of the diaphragm, it will reduce the air permeability of the diaphragm, thereby reducing the conductivity of the battery, and still have a negative impact on the charge and discharge performance of the battery. In view of this, developing a new method of adding a polymer coating to the ceramic coating to achieve a better balance between improving the adhesion of the diaphragm, maintaining air permeability and low powder loss rate has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] The present invention aims at the technical problem that adding a polymer coating to the ceramic coating of the existing lithium-ion battery separator affects the permeability of the separator, and provides a coated battery separator, a preparation method and a secondary battery. The improved technical scheme improves the adhesion of the separator while achieving a balance between the adhesion strength, permeability and powder loss rate of the separator, thereby further improving the battery performance.

[0006] In order to solve the above technical problems, the present invention provides a coated battery separator, comprising a base film and a coating coated on at least one surface of the base film, wherein the coating is a ceramic coating, the ceramic coating contains inorganic particles, and a plurality of sticky microspheres are embedded in the ceramic coating; the contact surface between the ceramic coating and the base film is the inner surface, and the other opposite surface is the outer surface, a plurality of the sticky microspheres protrude from the outer surface, and the ratio of the sum of the volumes of the portions of the sticky microspheres protruding from the outer surface to the total volume of the sticky microspheres is 0.2 to 0.8, preferably 0.25 to 0.75.

[0007] Preferably, 40-90% of the adhesive microspheres protrude from the outer surface of the ceramic coating, and the remaining adhesive microspheres are buried below the outer surface, and more preferably 50-80%.

[0008] Preferably, the material of the inorganic particles includes one or more of α-alumina, γ-alumina, boehmite, calcium carbonate, barium sulfate, barium titanate, hydrotalcite, montmorillonite, spinel, titanium dioxide, silicon dioxide, zirconium dioxide, magnesium oxide, calcium oxide, beryllium oxide, magnesium hydroxide, calcium hydroxide and silicon carbide; the D of the inorganic particles V50 The thickness of the ceramic coating is 1 to 2.5 μm.

[0009] Preferably, the sticky microspheres are polymer microspheres, and their materials include one or more of polyimide, styrene-butadiene rubber, modified polyacrylate, polyetherimide, aramid, aramid fiber, polyvinylidene fluoride, polymethyl methacrylate, thermoplastic polyurethane elastomer rubber, polyethylene terephthalate, polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene; further preferably, the sticky microspheres are made of polymethyl methacrylate (PMMA, Poly(methyl methacrylate)).

[0010] As the preferred PMMA microsphere, the glass transition temperature of the PMMA is 30 to 110° C., more preferably 40 to 60° C.; the median particle size D of the PMMA microsphere is V50The particle size is 1 to 10 μm, preferably 1 to 8 μm, and more preferably 1.5 to 5 μm, and the sedimentation percentage is 2 to 5% every seven days.

[0011] Preferably, the base film is made of polyethylene and / or polypropylene, and has a thickness of 5 to 15 μm.

[0012] Preferably, the solid matter mass ratio of the inorganic particles to the adhesive microspheres is 5:1 to 40:1, more preferably 5:1 to 25:1.

[0013] As a preferred embodiment of the above technical solution, the ceramic coating is coated on one or both surfaces of the base film.

[0014] The present invention also provides a method for preparing the aforementioned coated battery separator, comprising at least the following steps:

[0015] Preparation of slurry: Inorganic particles are mixed and dispersed with water to form an inorganic dispersion, and then a solution of viscous microspheres is added, dispersed evenly and sieved to obtain a mixed coating slurry;

[0016] Coating slurry: coating the mixed slurry onto the base film to form a ceramic coating layer embedded with inorganic particles on the base film;

[0017] Drying: drying the base film formed with the ceramic coating after coating to obtain a coated battery separator;

[0018] The sticky microspheres are PMMA microspheres, and the solid content of PMMA in the sticky microsphere solution is 10-40%; more preferably, the sedimentation percentage of the PMMA microspheres is 2-5% every seven days.

[0019] Preferably, in the slurry coating step, a coater is used to coat the mixed slurry onto the base film, the depth of the coater gravure roller is 20 to 100 μm, and the coating speed is 50 to 250 m / min, more preferably 100 to 150 m / min.

[0020] Preferably, the mixed coating slurry further comprises one or more of a thickener, a binder, a wetting agent and a dispersant.

[0021] As a further preferred embodiment of the mixed coating slurry, the dry weight of the mixed coating slurry is 100, and the mixed coating slurry includes the following components in mass percentage: 0.1 to 25 parts of sticky microspheres, 45 to 99 parts of inorganic particles, 0 to 10 parts of binder, 0 to 10 parts of thickener, 0 to 3 parts of wetting agent, and 0 to 3 parts of dispersant.

[0022] As further preferred mixed coating slurry:

[0023] The binder is one or more of styrene-butadiene rubber, polyacrylate, polyvinyl alcohol, polyacrylonitrile, polyvinylidene fluoride, polyacrylic acid, polyethylene oxide and polytetrafluoroethylene;

[0024] The thickener is one or more of sodium carboxymethyl cellulose, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium alginate, polyacrylamide, polyacrylic acid, polyvinyl alcohol, polyimide and cellulose;

[0025] The wetting agent is one or more of anionic surfactants, polyethylene surfactants and polyol surfactants, preferably polyether-modified siloxane or alkylphenol polyoxyethylene ether;

[0026] The dispersant is one or more of polyvinylpyrrolidone, polyacrylamide and polyvinyl alcohol.

[0027] As a preferred embodiment of the above technical solution, in the slurry coating step, the mixed slurry is coated on one or both surfaces of the base film to form a base film with a single-sided or double-sided ceramic coating, respectively.

[0028] The present invention also provides a secondary battery, comprising the aforementioned coated battery separator, or comprising the coated battery separator prepared by the aforementioned coated battery separator preparation method.

[0029] The above technical solution of the test example of the present invention develops a coated battery separator. When the ceramic functional coating is coated on the base film, the sticky microspheres, usually PMMA microspheres, are mixed in the slurry, and the ceramic material containing the sticky microspheres is coated on the surface of the base film by gravure roller coating to form a ceramic coating. By controlling the slurry components and preparation parameters, the distribution of the sticky microspheres in the ceramic coating of the separator is regulated, and the beneficial effects are:

[0030] The present invention embeds and distributes the sticky microspheres in the ceramic coating instead of completely covering the surface of the ceramic coating; some of the sticky microspheres protrude from the outer surface of the ceramic coating, which can provide a considerable amount of single-point bonding area for the diaphragm, effectively improving the bonding strength of the diaphragm. At the same time, because the sticky microspheres do not completely cover the surface of the ceramic coating, the diaphragm retains higher air permeability, higher electrical conductivity, and better thermal stability, thereby balancing the adhesion, air permeability and powder loss rate of the diaphragm and optimizing the performance of the battery diaphragm.

[0031] Additional aspects and advantages of the present invention will be set forth in part in the following description and in part will be obvious from the following description, or may be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The following drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the specific implementation methods, they are used to explain the present invention but do not constitute a limitation of the present invention. They include:

[0033] Figure 1 This is a schematic diagram of the structure of the viscous microspheres embedded in the ceramic coating in the coated battery separator of the present invention:

[0034] Wherein, R is the radius of the sticky microsphere, Δh is the height of the sticky microsphere protruding from the upper surface of the ceramic coating, h is the embedding depth of the sticky microsphere into the ceramic coating, and H is the thickness of the ceramic coating. DETAILED DESCRIPTION

[0035] In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail with reference to the accompanying drawings and specific test examples. It should be understood that the specific implementation methods described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0036] In response to the existing technical problems, the first aspect of the present invention provides a coated battery separator, comprising a base film and a coating coated on at least one surface of the base film, wherein the coating is a ceramic coating, the ceramic coating contains inorganic particles, and a plurality of sticky microspheres are embedded in the ceramic coating; the contact surface between the ceramic coating and the base film is the inner surface, and the other opposite surface is the outer surface, a plurality of sticky microspheres protrude from the outer surface, and the ratio of the sum of the volumes of the portions of the sticky microspheres protruding from the outer surface to the total volume of the sticky microspheres is 0.2 to 0.8, such as the volume proportion can be 0.2, 0.3, 0.35, 0.4, 0.5, 0.6, 0.75 and 0.8, and the volume proportion range is preferably 0.25 to 0.75.

[0037] As a preferred embodiment of the present invention, 40 to 90% of the sticky microspheres protrude from the outer surface of the ceramic coating, and the remaining sticky microspheres are buried below the outer surface. For example, the amount can be 40%, 50%, 52%, 60%, 66%, 70%, 72%, 79%, 80%, 85% and 90%, with 50 to 80% being more preferred.

[0038] As a preferred embodiment of the present invention, the material of the inorganic particles includes one or more of α-alumina, γ-alumina, boehmite, calcium carbonate, barium sulfate, barium titanate, hydrotalcite, montmorillonite, spinel, titanium dioxide, silicon dioxide, zirconium dioxide, magnesium oxide, calcium oxide, beryllium oxide, magnesium hydroxide, calcium hydroxide and silicon carbide; the D of the inorganic particles V50The thickness of the ceramic coating is 0.05-1.5 μm, such as 0.05 μm, 0.1 μm, 0.2 μm, 0.25 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm and 1.5 μm, and 0.1-1.0 μm is more preferred; the thickness of the ceramic coating is 1-2.5 μm, such as 1 μm, 1.2 μm, 1.5 μm, 1.7 μm, 1.8 μm, 2.0 μm, 2.2 μm and 2.5 μm.

[0039] As a preferred embodiment of the present invention, the sticky microspheres are polymer microspheres, and their materials include one or more of polyimide, styrene-butadiene rubber, modified polyacrylate, polyetherimide, aramid, aromatic sulfone, polyvinylidene fluoride, polymethyl methacrylate, thermoplastic polyurethane elastomer rubber, polyethylene terephthalate, polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene.

[0040] As a more preferred embodiment of the viscous microspheres, the viscous microspheres are microspheres made of polymethyl methacrylate (PMMA). The glass transition temperature Tg of PMMA material is 30 to 110°C, such as 30°C, 40°C, 45°C, 50°C, 55°C, 60°C, 70°C, 80°C, 90°C, 100°C and 110°C. In a more preferred embodiment, Tg can be limited to 40 to 60°C. Generally, the larger the Tg value of the viscous microsphere PMMA, the better the heat shrinkage and the smaller the compression rate of the diaphragm, and the smaller the Tg value, the greater the wet adhesive bond strength of the diaphragm; the median particle size Dv50 of the PMMA microspheres is 1 to 10 μm, such as 1 μm, 1.5 μm, 2 μm, 3 μm, 4μm, 5μm, 6μm, 7μm, 8μm and 10μm, with 1-8μm being better, and can be further limited to 1.5-5μm; the sedimentation percentage of PMMA microspheres is 2-5% every seven days, for example, it can be 2%, 3%, 4%. If the sedimentation percentage of PMMA microspheres is too small, the volume proportion of the part of the microspheres protruding from the outer surface will be increased, thereby seriously affecting the powder loss rate of the diaphragm; if the sedimentation percentage of PMMA microspheres is too large, the volume proportion of the part of the microspheres protruding from the outer surface will be reduced, thereby seriously affecting the bonding strength of the diaphragm.

[0041] As a preferred embodiment of the present invention, the material of the base film is polyethylene and / or polypropylene, and the thickness of the base film is 5 to 15 μm, such as 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm and 15 μm.

[0042] As a preferred embodiment of the present invention, the solid matter mass ratio of inorganic particles to sticky microspheres is 5:1 to 40:1, such as 5:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 18:1, 20:1, 25:1, 30:1, 35:1 and 40:1, and an appropriate selection can be made according to actual needs.

[0043] As a preferred embodiment of the present invention, a ceramic coating is coated on one or both surfaces of the base film, and adhesive microspheres are embedded in each ceramic coating.

[0044] In view of the existing technical problems, the second aspect of the present invention provides a method for preparing the aforementioned coated battery separator, which comprises at least the following steps:

[0045] S1: preparing a slurry, that is, mixing and dispersing inorganic particles with water to form an inorganic dispersion, and then adding a solution of viscous microspheres, dispersing evenly and sieving to obtain a mixed coating slurry;

[0046] S2: coating the slurry, i.e. coating the mixed slurry onto the base film to form a ceramic coating embedded with inorganic particles on the base film;

[0047] S3: drying, i.e. drying the base film formed with the ceramic coating after coating to obtain a coated battery separator.

[0048] The sticky microspheres are PMMA microspheres. The solid content of PMMA in the sticky microsphere solution is 10-40%, such as 10%, 15%, 20%, 25%, 30%, 35% and 40%. The solid content will directly affect the floating degree of PMMA microspheres. The higher the solid content, the smaller the floating degree, and the lower the solid content, the higher the floating degree. By limiting the range of solid content, PMMA microspheres are solidified inside the coating to avoid floating and sinking. The sedimentation percentage of PMMA microspheres is 2-5% every seven days. Generally, the larger the particle size of the microspheres and the more uneven the particle distribution, the easier it is for the microspheres to settle. The following method can be used to measure the sedimentation percentage:

[0049] Add 100mL of PMMA solution to a 100mL test tube and observe it at room temperature for 7 days. The lower layer of the supernatant in the test tube is read as h1. The sedimentation rate is:

[0050]

[0051] As a preferred implementation scheme of the method of the present invention, in step S2, a coater is used to coat the mixed slurry onto the base film, and the depth of the coater gravure roller is 20 to 100 μm, such as 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm and 100 μm; the coating speed is 50 to 250 m / min, such as 50 m / min, 100 m / min, 150 m / min, 200 m / min and 250 m / min. A better implementation scheme can further limit the coating speed to 100 to 150 m / min.

[0052] As a preferred embodiment of the method of the present invention, the mixed slurry in step S1 further comprises one or more of a thickener, a binder, a wetting agent and a dispersant, and the dry weight of the mixed slurry is 100, wherein the components and their mass fractions are:

[0053] 0.1 to 25 parts of adhesive microspheres, for example, 0.1, 1, 2, 4, 6, 7, 8, 10, 15, 20 and 25 parts can be selected;

[0054] Inorganic particles 45-99 parts, such as 45, 50, 55, 60, 65, 70, 75, 80, 85, 86, 87, 88, 89, 90 and 99 parts can be selected:

[0055] The binder is 0 to 10 parts, such as 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10 parts; the binder is one or more of styrene-butadiene rubber, polyacrylate, polyvinyl alcohol, polyacrylonitrile, polyvinylidene fluoride, polyacrylic acid, polyethylene oxide and polytetrafluoroethylene. When the binder is selected from polyacrylate and polyacrylic acid, the mass ratio thereof can be 1:1 to 1:2.

[0056] The thickener is 0-10 parts, such as 0, 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10 parts can be selected; the thickener is one or any combination of sodium carboxymethyl cellulose, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium alginate, polyacrylamide, polyacrylic acid, polyvinyl alcohol, polyimide and cellulose.

[0057] The wetting agent is 0N3 parts, such as 0, 1, 2 and 3 parts can be selected; the wetting agent is one or any combination of anionic surfactants, polyethylene surfactants and polyol surfactants, such as polyether-modified siloxane or alkylphenol polyoxyethylene ether.

[0058] The dispersant is 0N3 parts, such as 0, 1, 2 and 3 parts can be selected; the dispersant is one or any combination of polyvinylpyrrolidone, polyacrylamide and polyvinyl alcohol.

[0059] The solvent is 100 to 300 parts, such as 100, 150, 200, 250 and 300 parts; more preferably, the solvent is 150 to 250 parts; the solvent can be pure water.

[0060] As a preferred embodiment of the method of the present invention, in step S2, the mixed coating slurry is coated on one or both surfaces of the base film to form a base film having a single-sided or double-sided ceramic coating, respectively.

[0061] In view of the existing technical problems, the third aspect of the present invention provides a secondary battery, comprising the aforementioned coated battery separator, or comprising a coated battery separator prepared by the aforementioned coated battery separator preparation method.

[0062] The following are specific test examples and comparative examples of the present invention. Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art. The parts referred to below are all measured by mass, with ultrapure water as the mass standard.

[0063] Test Example 1:

[0064] Boehmite (γ-AlOOH, hydrated alumina; manufacturer: Anhui Yishitong Company, BG611, D V50 0.8 μm) and polyvinylpyrrolidone were dispersed in water, and dispersed by sand mill (speed of 1000 rpm, 30 min) to form a dispersion, and polymethyl methacrylate (Shenzhen Haodian Technology Co., Ltd., SWA709, Tg = 40 ° C, D V50 =2μm, sedimentation ratio 3%), after being evenly dispersed, acrylate, sodium carboxymethyl cellulose and polyether modified siloxane are added in sequence, dispersed evenly and sieved to form a mixed coating slurry. Among them, the dry weight mass ratio of boehmite, PMMA, binder, thickener, wetting agent and dispersant is 88:6:3:2.6:0.2:0.2.

[0065] The mixed coating slurry was coated on both sides of the base film by a coating machine at a coating speed of 150 m / min, and then dried to form a mixed coating layer with a thickness of 1.5 μm+1.5 μm.

[0066] Test Example 2:

[0067] The main differences from Test Example 1 are:

[0068] The Tg of polymethyl methacrylate added to the dispersion is 55° C.; the mass ratios of boehmite, PMMA, binder, thickener, wetting agent and dispersant are 86:8:3:2.6:0.2:0.2, respectively.

[0069] Test Example 3:

[0070] The main differences from Test Example 1 are:

[0071] The polymethyl methacrylate added to the dispersion has a Tg of 50°C and a sedimentation ratio of 2%.

[0072] Test example 4:

[0073] The main differences from Test Example 1 are:

[0074] The polymethyl methacrylate added to the dispersion has a Tg of 50°C and a sedimentation ratio of 4%.

[0075] Test Example 5:

[0076] The main differences from Test Example 1 are:

[0077] The mixed slurry is coated on one side of the base film.

[0078] The polymethyl methacrylate added to the dispersion has a Tg of 60°C and a sedimentation ratio of 5%.

[0079] Test Example 6:

[0080] The main differences from Test Example 1 are:

[0081] The polymethyl methacrylate added to the dispersion has a Tg of 30°C and a sedimentation ratio of 1%.

[0082] Comparative Example 1:

[0083] The main differences from Test Example 1 are:

[0084] The polymethyl methacrylate added to the dispersion has a Tg of 60°C and a sedimentation ratio of 6%.

[0085] The parameter settings not described in detail in the above test examples and comparative examples are detailed in Table 1 and will not be repeated here.

[0086] For each example, the data obtained through the performance test include air permeability increase, embedding depth h, bonding strength, powder loss rate, thermal shrinkage rate (MD150℃ and TD150℃), ionic conductivity, ratio of microsphere protrusion volume to total volume R V The specific test method is as follows:

[0087] (1) Air permeability (s / (100cc))

[0088] The test was conducted in accordance with the requirements of GB / T36363-2018. A 600mm×100mm membrane sample was cut and tested using a Wangyan air permeability meter (Asahi Co., Ltd., EG01-55-1MR) for 3 seconds. The air permeability of the membrane was measured at any position with an interval of 100mm along the 600mm TD direction. The average value of the above five test points was recorded as the membrane air permeability.

[0089] (2) Embedment depth h (μm)

[0090] The embedding depth h is the vertical distance between the bottom of the sticky microsphere and the outer surface where it is embedded. Ten 5 cm × 5 cm coated membrane samples were cut, 5 of which were cut vertically along the TD direction. The vertical distance between the bottom of the sticky microsphere marked as i and the outer surface of the coating within the scope of the microscope was measured using a Zeiss field emission scanning electron microscope (ZEISS SIGMA 300 at 500 times the field of view of the electron microscope) and recorded as the embedding depth h. i1 , the embedding depth of all microspheres in the TD section Test 5 samples and take the average value h TD′ The other 5 samples were cut vertically along the MD direction and measured using a Zeiss field emission scanning electron microscope (ZEISSSIGMA 300, 500 times the field of view of the electron microscope). The vertical distance between the bottom of the sticky microsphere marked as i and the outer surface of the coating was recorded as the embedding depth h. i2 , the embedding depth of all microspheres in the MD section Test 5 samples and take the average value h MD′ ; The calculated embedding depth h is:

[0091]

[0092] (3) Wet adhesive strength (MPa·S)

[0093] Cut samples of 20mm×60mm size, pole pieces of 20mm×60mm size and PET of 20mm×60mm size, stack them in the order of diaphragm, pole piece and PET, put them into 80mm×80mm aluminum-plastic bag, inject 1.5g electrolyte (LiPF6 1M, EC:EMC=3 / 7, VC=2%), seal the edges with vacuum (-80kPa), and ripen for 24h; pad the top and bottom of the sample with silicone pads, use a hot press (Qmesys, QM940AS) for 10min, where the upper and lower clamps of the hot press are at 60℃ and the pressure is 200kgf. After cooling, take the sample out of the aluminum-plastic bag, peel off the PET manually, and clamp the electrode with the lower chuck of the tensile machine (Jinan Sike Testing Technology Co., Ltd., TSL-1002), and clamp the diaphragm with the upper chuck to ensure no tilt. The tensile speed is 300mm / min, measure three times, and take the average value.

[0094] (4) Powder loss rate (%)

[0095] Cut the battery diaphragm into 6 pieces of 3cm×22cm size, place them on an analytical balance and weigh them, and record the weight as m1; ensure that the curved table of the friction color fastness tester (Daei Science Seiki Manufacturing Co., Ltd., RT-300S) is clean, fix the lens paper on the friction head of the friction color fastness tester, with the smooth side of the lens paper facing outward, and then fix the cut battery diaphragm on the curved table of the friction color fastness tester, with one side of the heat-resistant coating facing up, clamp it and gently place the friction head on the diaphragm, set the number of experiments to 5 on the operation panel of the color fastness tester and click to start. After the experiment is completed, take out the battery diaphragm, place it on an analytical balance and weigh it, and record the weight as m2. The powder loss amount M=m1-m2, take the average value of the six groups of diaphragm test data, and the powder loss rate is:

[0096]

[0097] If the diaphragm is a double-layer coating on both sides of the base film, the weight of the diaphragm after friction test on both sides is m2, and the powder loss rate data is calculated based on this.

[0098] (5) Thermal shrinkage (%):

[0099] The test was conducted in accordance with the requirements of GB / T36363-2018. A sample of 10 cm × 10 cm was cut, and the horizontal TD and vertical MD directions were marked on the sample. The horizontal and vertical widths were measured using a fully automatic image measuring projector (Kunshan Gaopin Precision Instrument Co., Ltd., GP-300C). The sample was clamped between two sealed A4 papers, and placed in a 150°C oven for 1 hour. After the sample returned to room temperature, the horizontal and vertical widths were measured using a fully automatic image measuring projector. The measurements were performed three times, and the average value was taken.

[0100]

[0101] (6) Ionic conductivity σ (S / m):

[0102] Cut a sample of 100mm×100mm size, ensure that there is no foreign matter on the surface of the insulation resistance test bench, place the sample in the specified area of ​​the test bench, start the YD9820A program-controlled insulation resistance tester (Changzhou Yangzi Electronics Co., Ltd.) for testing, voltage 100V, time 5s, pressure 0.05MPa, test 5 groups of resistance values ​​R, take the average value, the conductivity is:

[0103]

[0104] Where S is the cross-sectional area and L is the length.

[0105] (7) Ratio of the protruding volume of the microsphere to the total volume V

[0106] After measuring the embedding depth h of the sticky microsphere, the corresponding relationship between the embedding depth and the protruding outer surface volume of the sticky microsphere is as follows:

[0107] Since the viscous microspheres are approximately spherical, the part of the viscous microspheres protruding from the outer surface of the ceramic coating can be regarded as a spherical part, and the volume of the spherical part is related to the embedding depth h of the viscous microspheres. The thickness of the ceramic coating is H, h≤H, D V50 is the median particle size of all the adhesive microspheres.

[0108] Assume that the height of the top of a sticky microsphere protruding from the outer surface relative to the outer surface is h0, and the radius of the sticky microsphere is R0. It is estimated that R0 = 1 / 2D V50 , then h0=2R0-h, the volume V of the viscous microsphere 球 for:

[0109]

[0110] The volume V of the spherical defect of the sticky microsphere protruding from the outer surface 凸 for:

[0111]

[0112] Take n sticky microspheres as samples and calculate the ratio of the volume of the sphere to the total volume of the sticky microspheres R V for:

[0113]

[0114] Usually n = 10 is taken to calculate the total R of the sticky microspheres. V By calculation, it can be obtained that when 0.2≤R V When ≤0.8, the embedding depth h satisfies 1 / 3D V50 ≤h≤D V50 .

[0115] (8) The number of sticky microspheres protruding from the outer surface of the ceramic coating

[0116] Ten 5 cm × 5 cm diaphragm samples were cut, of which five were cut vertically along the TD direction. A Zeiss field emission scanning electron microscope (ZEISS SIGMA 300, 500 times the field of view) was used to observe the range of the microscope. The number of sticky microspheres was recorded as n1, the number of sticky microspheres protruding from the outer surface of the ceramic coating was recorded as n2, and the proportion of sticky microspheres protruding from the outer surface of the ceramic coating in the TD direction was n. TD =n2 / n1, repeat the test for 5 groups of samples and take the average value;

[0117] Another 5 samples were cut vertically along the MD direction and observed using a Zeiss field emission scanning electron microscope (ZEISSSIGMA 300, 500 times the field of view). The number of sticky microspheres within the scope of the microscope was recorded as n3, the number of sticky microspheres protruding from the outer surface of the ceramic coating was recorded as n4, and the proportion of sticky microspheres protruding from the outer surface of the ceramic coating in the MD direction was n. MD =n4 / n3, repeat the test for 5 groups of samples and take the average value, then the proportion of microspheres protruding from the outer surface of the ceramic coating is (n TD +n MD ) / 2.

[0118] The battery separators prepared in the test examples and comparative examples were subjected to performance tests, and the test results are shown in the following table:

[0119] Table 1: Comparison of physical properties of test examples and comparative examples

[0120]

[0121]

[0122] Table 1 continued:

[0123]

[0124]

[0125] From Table 1 above, combined with the test examples and comparative examples, it can be seen that: the lower the mass proportion of inorganic particles (boehmite) in the mixed slurry, the smaller the ionic conductivity of the corresponding diaphragm; the ionic conductivity decreases with the increase of the permeability value; when the ratio of the protruding volume of the microspheres to the total volume R V Limited to the range of 0.2 to 0.8, on the basis of obtaining higher membrane bonding strength, the ionic conductivity is increased, and while being able to take into account appropriate air permeability value-added, it has greater bonding strength, smaller powder loss rate, smaller thermal shrinkage and higher thermal stability.

[0126] In the description of the present invention, it should be noted that the terms "inside", "outside", "vertical", etc., indicating directions or positional relationships, are only for the convenience of describing the present invention, and do not indicate or imply that the devices or elements referred to must have a specific direction or be constructed and operated in a specific direction, and therefore cannot be understood as limiting the present invention. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0127] Although the test examples of the present invention have been shown and described above, it can be understood that the above test examples are illustrative and cannot be construed as limitations of the present invention. Ordinary technicians in the field can change, modify, replace and modify the above test examples within the scope of the present invention.

Claims

1. A coated battery separator, comprising a base film and a coating coated on at least one surface of the base film, wherein the coating is a ceramic coating, and the ceramic coating contains inorganic particles, characterized in that: A number of sticky microspheres are embedded in the ceramic coating; the contact surface between the ceramic coating and the base film is the inner surface, and the other opposite surface is the outer surface. A number of the sticky microspheres protrude from the outer surface, and the ratio of the sum of the volumes of the parts of the sticky microspheres protruding from the outer surface to the total volume of the sticky microspheres is 0.2 to 0.

8.

2. The coated battery separator according to claim 1, characterized in that The ratio of the sum of the volumes of the portions of the viscous microspheres protruding from the outer surface to the total volume of the viscous microspheres is 0.25 to 0.

75.

3. The coated battery separator according to claim 1, characterized in that 40 to 90% of the adhesive microspheres protrude from the outer surface of the ceramic coating, and the remaining adhesive microspheres are buried below the outer surface.

4. The coated battery separator according to claim 1, characterized in that The material of the inorganic particles includes one or more of α-alumina, γ-alumina, boehmite, calcium carbonate, barium sulfate, barium titanate, hydrotalcite, montmorillonite, spinel, titanium dioxide, silicon dioxide, zirconium dioxide, magnesium oxide, calcium oxide, beryllium oxide, magnesium hydroxide, calcium hydroxide and silicon carbide. The Dv of the inorganic particles is 50 The thickness of the ceramic coating is 1 to 2.5 μm.

5. The coated battery separator according to claim 1, characterized in that The viscous microspheres are polymer microspheres, and their materials include one or more of polyimide, styrene-butadiene rubber, modified polyacrylate, polyetherimide, aramid, aramid sulfone, polyvinylidene fluoride, polymethyl methacrylate, thermoplastic polyurethane elastomer rubber, polyethylene terephthalate, polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene.

6. The coated battery separator according to claim 5, characterized in that The viscous microspheres are polymethyl methacrylate microspheres, and the glass transition temperature of the polymethyl methacrylate is 30 to 110° C.; the D v50 The particle size of the polymethyl methacrylate microspheres is 1 to 10 μm; and the sedimentation percentage of the polymethyl methacrylate microspheres is 2 to 5% every seven days.

7. The coated battery separator according to claim 1, characterized in that The base film is made of polyethylene and / or polypropylene, and has a thickness of 5 to 15 μm.

8. The coated battery separator according to claim 1, characterized in that The solid matter mass ratio of the inorganic particles to the adhesive microspheres is 5:1 to 40:1, preferably 5:1 to 25:

1.

9. The coated battery separator according to any one of claims 1 to 8, characterized in that: The ceramic coating is coated on one or both surfaces of the base film.

10. A method for preparing a coated battery separator according to any one of claims 1 to 9, characterized in that: At least the following steps are included: Preparation of slurry: Inorganic particles are mixed and dispersed with water to form an inorganic dispersion, and then a solution of viscous microspheres is added, dispersed evenly and sieved to obtain a mixed coating slurry; Coating slurry: coating the mixed slurry onto the base film to form a ceramic coating layer embedded with inorganic particles on the base film; Drying: drying the base film formed with the ceramic coating after coating to obtain a coated battery separator; The sticky microspheres are polymethyl methacrylate microspheres, the sedimentation percentage of which is 2-5% every seven days, and the solid content of polymethyl methacrylate in the sticky microsphere solution is 10-40%; The mixed coating slurry further comprises one or more of a thickener, a binder, a wetting agent and a dispersant; Based on the dry weight of the mixed coating slurry as 100, the mixed coating slurry includes the following components in mass percentage: 0.1 to 25 parts of sticky microspheres, 45 to 99 parts of inorganic particles, 0 to 10 parts of a binder, 0 to 10 parts of a thickener, 0 to 3 parts of a wetting agent, and 0 to 3 parts of a dispersant; In the slurry coating step, a coating machine is used to coat the mixed slurry onto the base film, the depth of the gravure roller of the coating machine is 20 to 100 μm, and the coating speed is 50 to 250 m / min.

11. The method for preparing a coated battery separator according to claim 10, characterized in that: The binder is one or any combination of styrene-butadiene rubber, polyacrylate, polyvinyl alcohol, polyacrylonitrile, polyacrylic acid, polyvinylidene fluoride, polyethylene oxide and polytetrafluoroethylene; the thickener is one or any combination of sodium carboxymethyl cellulose, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium alginate, polyacrylamide, polyacrylic acid, polyvinyl alcohol, polyimide and cellulose; the wetting agent is one or any combination of anionic surfactant, polyethylene surfactant and polyol surfactant; the dispersant is one or any combination of polyvinylpyrrolidone, polyacrylamide and polyvinyl alcohol.

12. The method for preparing a coated battery separator according to any one of claims 10 to 11, characterized in that: In the slurry coating step, the mixed slurry is coated on one or both surfaces of the base film.

13. A secondary battery, characterized in that: The invention comprises the coated battery separator according to any one of claims 1 to 9, or comprises the coated battery separator prepared by the method for preparing the coated battery separator according to any one of claims 10 to 12.

Citation Information

Patent Citations

  • Battery diaphragm, preparation method thereof and battery

    CN116454542A

  • Battery diaphragm, secondary battery and electric equipment

    CN117937048A

  • Lithium ion battery diaphragm, preparation method thereof and lithium ion battery

    CN117977102A

  • Separator for lithium secondary battery and a method of making the same

    KR1020160118979A